2012
DOI: 10.4300/jgme-d-11-00158.1
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Multifaceted Quality-Improvement Curriculum in an Obstetrics-Gynecology Resident Continuity-Clinic Setting: A 4-Year Experience

Abstract: Background Although many residency programs are instituting quality improvement (QI) curricula in response to both institutional and external mandates, there are few reports of successful integration of resident initiated projects into these QI curricula with documented impact on health care processes and measures. Intervention We introduced a multifaceted curriculum into an Obstetrics-Gynecology continuity clinic. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…While the curriculum incorporated some didactics, the emphasis was on skill development in the form of resident-led QI projects. 15,[17][18][19][20][21] This longitudinal curriculum also…”
Section: Methodsmentioning
confidence: 99%
“…While the curriculum incorporated some didactics, the emphasis was on skill development in the form of resident-led QI projects. 15,[17][18][19][20][21] This longitudinal curriculum also…”
Section: Methodsmentioning
confidence: 99%
“…Since 2000, a growing body of literature has investigated PSQI education in GME, with notable progress in surgical disciplines in recent years . Nonetheless, PSQI education rarely appeared in otolaryngology literature until 2016.…”
Section: Introductionmentioning
confidence: 99%
“…4 Since 2000, a growing body of literature has investigated PSQI education in GME, [5][6][7][8][9][10][11][12][13][14] with notable progress in surgical disciplines in recent years. [15][16][17][18][19] Nonetheless, PSQI education rarely appeared in otolaryngology literature until 2016. We therefore developed and implemented a formal PSQI curriculum for otolaryngology residents and compared outcomes against a matched control program using validated instruments.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Existing publications often describe resident QI activities offered through dedicated electives, 6-12 some limited to 1 postgraduate (PGY) level, 13 with only a few describing longitudinal QI curricula. 12,[14][15][16] Most studies report on hospital-based QI, with relatively few emphasizing ambulatory care, 9,12,17 and only a minority report on patient care improvement. 9,12,15,17,18 A study of family medicine graduates found that some reported doing QI without formal training, while others were not engaged in improvement activities even after didactic QI exposure.…”
Section: Introductionmentioning
confidence: 99%
“…12,[14][15][16] Most studies report on hospital-based QI, with relatively few emphasizing ambulatory care, 9,12,17 and only a minority report on patient care improvement. 9,12,15,17,18 A study of family medicine graduates found that some reported doing QI without formal training, while others were not engaged in improvement activities even after didactic QI exposure. 19 We hypothesized that a longitudinal, 3-year QI immersion model, integrated into an ambulatory block schedule, with didactic and experiential components, spanning outpatient and inpatient sites, could be used to teach QI to internal medicine residents.…”
Section: Introductionmentioning
confidence: 99%